2022
DOI: 10.18632/aging.203956
|View full text |Cite
|
Sign up to set email alerts
|

Association between social isolation and reduced mental well-being in Swedish older adults during the first wave of the COVID-19 pandemic: the role of cardiometabolic diseases

Abstract: Social isolation has been recommended as a strategy for reducing COVID-19 risk, but it may have unintended consequences for mental well-being. We explored the relationship between social isolation and symptoms of depression and anxiety in older adults during the first wave of the COVID-19 pandemic and assessed the role of cardiometabolic diseases (CMDs) in this association. Between May and September 2020, 1,190 older adults from the Swedish National Study on Aging and Care in Kungsholmen were surveyed about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…Another review (10) shows that this population is more likely to suffer mental health issues associated with Covid-19, and that the older population experienced e.g., stress, depression, anxiety, and loneliness during the pandemic. Comparable results were found in a Swedish study (11) among seniors in an urban setting. However, in a Swedish longitudinal study from 2021, where very early effects of the pandemic on 65-71-year-olds were investigated, results show an equal well-being in the population, or even higher, as before the pandemic (12).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Another review (10) shows that this population is more likely to suffer mental health issues associated with Covid-19, and that the older population experienced e.g., stress, depression, anxiety, and loneliness during the pandemic. Comparable results were found in a Swedish study (11) among seniors in an urban setting. However, in a Swedish longitudinal study from 2021, where very early effects of the pandemic on 65-71-year-olds were investigated, results show an equal well-being in the population, or even higher, as before the pandemic (12).…”
Section: Introductionsupporting
confidence: 69%
“…Anxiety is common in the older population (16,17), and during the Covid − 19 pandemic an increase was likely to occur as this age group was especially vulnerable to the virus, more socially isolated, and the special situation of a pandemic is associated with uncertainty regarding both the present and the future. Studies performed during the Covid − 19 pandemic con rmed increased anxiety among the older adults (10,11,18). Our result re ects what other research have found and suggests that anxiety is of major concern when evaluating and predicting mental health in the older population during pandemic-like conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Even if precision shielding of the elderly can be achieved (as our data suggest), it is unknown whether it can be maintained effectively for pandemic-long circles lasting two or more years. Moreover, adverse consequences of trying to diminish exposures of vulnerable elderly may be substantial for their social well-being and their mental health [ 68 , 69 ]. Adverse consequences are likely for all age groups, including for children after school closures [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 Even if precision shielding of the elderly can be achieved (as our data suggest), it is unknown whether it can be maintained effectively for pandemic-long circles lasting 2 or more years. Moreover, adverse consequences of trying to diminish exposures of vulnerable elderly may be substantial for their social well-being and their mental health 30,31 . Adverse consequences are likely for all age groups, including for children after school closures 32 .…”
Section: Discussionmentioning
confidence: 99%